SISTEM PENDIDIKAN DI MESIR - Qolbiyah, Aini; Rajab, Khairunnas (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2022)
The aim of this study is to describe the learning system and curriculum that applies in Egypt, especially basic education of Kindergarten. The method used in this paper is descriptive qualitative and literature study. The main purpose of preschool education is to help children develop their general intelligence and improve their abilities and capacities. The interest of the Egyptian community to send their children to private kindergartens is 10%, in public kindergartens it is 18%, family planning is 58% and others (private tutoring/no school, etc.) are 18%. The position of public KG teacher it is mandatory to have at least a bachelor's degree with a specialization in early childhood education and development. The preparation of PAUD teachers at the university level lasts four years (8 semesters) and students must attend their classes every day. The Faculty of Education, Cairo University, provides a Professional Diploma Program to develop the skills of early childhood teachers.